Status and comparison of HIV Knowledge, HIV Testing and other healthy behavior between men who have sex with men only (MSMO) and men who have sex with men and women (MSMW): a cross-sectional study in Zhejiang Province, China - Zhongrong Yang; Lin Chen; Wanjun Chen; Lin He; Chengliang Chai (BMC Public Health)
Abstract Objective This study was conducted to explore the human immunodeficiency virus (HIV) status of and compare HIV knowledge, HIV testing, and other healthy behaviors between men who have sex with men and women (MSMW) and men who have sex with men only (MSMO), to provide a scientific basis for targeted HIV interventions for this population. Methods A cross-sectional survey was conducted to collect demographic and behavioral information using questionnaires for statistical analysis. Results Among 1,993 participants, 772 (38.7%) reported having sexual intercourse with women. The results of the multivariate logistic regression model analysis indicated that MSMW had a lower probability than MSMO of reporting HIV knowledge 1 (adjusted odds ratio [aOR]:0.556, 95% CI: 0.409–0.756), knowledge 2 (aOR:0.626; 95% CI, 0.515–0.761), knowledge 3 (aOR:0.569; 95% CI: 0.447–0.724), informing their HIV status to the last casual sex partners offline (aOR: 0.515, 95% CI: 0.358–0.743), HIV testing more than once in the past 6 months (aOR: 0.696, 95% CI: 0.521–0.931), and HIV testing in a hospital in the past 6 months (aOR: 0.696, 95% CI: 0.521–0.931). In contrast, MSMW had a higher probability of post-exposure prophylaxis (PEP) intake in the past 6 months (aOR: 2.252, 95% CI: 1.570–3.229), pre-exposure prophylaxis (PrEP) intake in the past 6 months (aOR: 1.630, 95% CI: 1.091–2.434), and cumulative HIV testing more than twice (aOR: 1.917, 95% CI: 1.434–2.563). Conclusion MSMW showed significant differences with MSMO in HIV knowledge and HIV related risky reduction behaviors. It is necessary to enhance awareness and skills on HIV self-testing, PEP, and PrEP among MSM. Encouraging HIV knowledge education and HIV testing service are important for MSMW. PEP and PrEP might be enhanced among MSMO for reducing the risk of HIV transmission.